Perbandingan Hasil Pemeriksaan Hemoglobin Secara Digital Terhadap Hasil Pemeriksaan Hemoglobin Secara Cyanmethemoglobin - Meimi Lailla; Z Zainar; Ade Fitri (UPT Laboratorium Terpadu, Universitas Diponegoro, 2021)
Background: Various methods of hb examination are used by health facilities in Indonesia. Examinations with auto analyzers that use the cyanmethemoglobin method are proven to be accurate and produce reliable measurements. A practical and easy to do hemoglobin check is the digital method (Hb meter). This study aims to determine the differences in the results of digital hb examination using capillary blood with the cyanmethemoglobin method using venous blood.Methods: This study is a comparative study using primary data. There were 30 respondents who were randomly taken in the Clinical Pathology laboratory of Arifin Achmad Hospital Riau Province. This research was conducted from August to September 2020 to analyze the data using unpaired numerical analytical tests.Results: Based on the independent t test, the p value was 0.651 (> 0.05), which means that there was no statistically significant difference in the hb levels in the two types of examinations